Efficacy of Potassium Hydroxide (KOH) on the Treatment of Condyloma Acuminata - Linda Julianti Wijayadi; Kelvin Kelvin; Charity Harlim (GLOBAL HEALTH SCIENCE GROUP, 2025)
Condyloma acuminata (CA) represents one of the most prevalent sexually transmitted infections globally. Current treatment modalities focus primarily on lesion removal rather than viral eradication, with no universally accepted gold standard therapy. Potassium hydroxide (KOH) has emerged as a promising alternative treatment option. Objective to systematically review the efficacy and safety of potassium hydroxide in treating condyloma acuminata compared to other established treatments. A systematic literature review was conducted using PubMed, Google Scholar, Science Direct, Wiley Online Library, and Cochrane Library databases. Search terms included combinations of